2018
DOI: 10.1111/vox.12697
|View full text |Cite
|
Sign up to set email alerts
|

In vitro quality of amotosalen‐UVA pathogen‐inactivated mini‐pool plasma prepared from whole blood stored overnight

Abstract: Frozen WB-derived AUVA-plasma prepared from mini-pools within 19 h of WB-collection met the quality standards required for TP and retained hemostatic capacity for up to 12 months. This product could provide a cost-effective convenient substitute for apheresis plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…A total reduction of variability of 55% (volume and coagulation factor concentration) between the units respectively was observed when the plasma units were produced by the novel approach of pooling five donor plasma units to gain six therapeutic plasma units in combination with AS pathogen inactivation. Moderate, but significant losses of coagulation factors (except for vWF) were observed post thawing of PTPs compared to fresh SDPs, findings which are in line with previously published data using amotosalen/UVA PI 12,19,20 and in compliance with European standards 21 . Also, a moderate prolongation of the coagulation time was observed, which is considered likely not being clinically relevant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A total reduction of variability of 55% (volume and coagulation factor concentration) between the units respectively was observed when the plasma units were produced by the novel approach of pooling five donor plasma units to gain six therapeutic plasma units in combination with AS pathogen inactivation. Moderate, but significant losses of coagulation factors (except for vWF) were observed post thawing of PTPs compared to fresh SDPs, findings which are in line with previously published data using amotosalen/UVA PI 12,19,20 and in compliance with European standards 21 . Also, a moderate prolongation of the coagulation time was observed, which is considered likely not being clinically relevant.…”
Section: Discussionsupporting
confidence: 91%
“…Amotosalen/UVA (AS) pathogen inactivation technology (INTERCEPT™ Blood System, Cerus Corporation), a targeted photochemical reaction irreversibly crosslinking nucleic acids, 11 allows the treatment of pools of five plasma units and splitting into six standardised therapeutic units 12 . The key objectives for this production method are the prevention of transmission of infectious agents and the preservation of the haemostatic capacity as well as the clinical effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show no significant decrease in proteins such as antithrombin and protein S that are integral to the clotting cascade. 91 It has been shown that for patients with congenital coagulation factor deficiencies, replacement of coagulation factors in INTERCEPT® plasma exhibited kinetics and therapeutic efficacy similar to conventional FFP. 92 Additionally, liver transplant and therapeutic plasma exchange studies have shown success for the INTERCEPT® system.…”
Section: Intercept® Plasmamentioning
confidence: 99%
“…92 Additionally, liver transplant and therapeutic plasma exchange studies have shown success for the INTERCEPT® system. 91,93…”
Section: Intercept® Plasmamentioning
confidence: 99%
“…The most studied plasma categories used in iTTP series are: (i) Solvent-Detergent-(SD) FFP, produced by industrial pooling of plasma sources from pools of 100 to 1.500 individual plasma collections or more, depending on the manufacturer, with pathogen inactivation by solvent and detergent treatment; and (ii) Quarantine-(Q) FFP, that has not been modified apart from freezing, thawing and retesting for a limited number of pathogens [19,24]. More recently, new forms of FPP have been made available, including individual or mini-pools of therapeutic plasma pathogen inactivated by Amotosalen-UVA [25]. Uses of different plasma categories in France has varied over time as recentmly discussed in [26].…”
Section: Introductionmentioning
confidence: 99%